Pengembangan e-LKPD Arthropoda berbasis Pendekatan Konstruktivisme Untuk Meningkatkan Hasil belajar: (Development of Arthropoda e-LKPD based on Constructivism Approach To Improve Learning Outcomes) - Putri Ramadhani; Muhammad Damris; Tedjo Sukmono (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2022)
Learning based on understanding is the result of the process of constructing knowledge, understanding and experiences of students. Materials Arthropods, especially insects and crustaceans are material close to everyday life. So that to make the learning process more interesting and motivate students and improve learning outcomes, e-LKPD teaching media is needed. The purpose of this study was to generate, determine the feasibility, and effectiveness of e-LKPD on learning outcomes. This research is a development research. This research design follows the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation and evaluation. The e-LKPD product before being tested was validated by material experts and media experts to determine the feasibility of the products made. e-LKPD Arthropoda was validated by media expert 1 with a final percentage of 87.75%, media expert 2 by 90,91% and material expert 94.31% very good category. Thus the e-LKPD product is said to be feasible. This product was then tested at SMAN 11 Muaro Jambi involving 2 biology subject teachers, a small group, 6 students, a large group of 20 students. The test results on teachers get a percentage of 89.37%. The results of small group trials get a percentage of 87.92%, large group trials get a percentage of 86.69% including the very good category. The use of Constructivism-based Arthropoda e-LKPD is effective in improving student learning outcomes. Key words: Arthropod,e-LKPD, Construtivism AbstrakÂ Program Studi Pendidikan Biologi FKIP Universitas Jambi, Jambi- Indonesia Â Pembelajaran berdasarkan pada pemahaman ialah hasil dari proses konstruksi pengetahuan, pemahaman dan pengalaman peserta didik. Materi Arthropoda khususnya insecta dan crustacea merupakan materi dekat dengan kehidupan sehari-hari. Sehingga untuk membuat proses pembelajaran menjadi lebih menarik minat dan motivasi peserta didik serta meningkatkan hasil belajar maka diperlukan media ajar e-LKPD. Tujuan penelitian ini adalah menghasilkan, mengetahui kelayakan, dan efektifitas e-LKPD terhadap hasil belajar. Penelitian ini merupakan penelitian pengembangan. Desain penelitian ini mengikuti model pengembangan ADDIE yang terdiri 5 tahap yaitu analisis, desain, pengembangan, implementasi dan evaluasi. Produk e-LKPD sebelum diujicobakan divalidasi oleh ahli materi dan ahli media untuk mengetahui kelayakan dari produk yang dibuat. e-LKPD Arthropoda divalidasi oleh ahli media 1 dengan persentase akhir 87,75%, ahli media 2 sebesar 90,91% dan ahli materi sebesar 94,31% kategori sangat baik. Dengan demikian produk e-LKPD dikatakan layak. Produk ini kemudian di ujicobakan di SMAN 11 Muaro Jambi melibatkan 2 orang guru mata pelajaran biologi, kelompok kecil, 6 orang peserta didik, kelompok besar 20 orang peserta didik. Hasil ujicoba pada guru mendapatkan persentase 89,37%. Hasil ujicoba kelompok kecil mendapatkan persentase 87,92%, ujicoba kelompok besar mendapatkan persentase 86,69% termasuk kategori sangat baik. Penggunaan e-LKPD Arthropoda berbasis Konstruktivisme efektif meningkatkan hasil belajar peserta didik. Kata kunci: Arthropoda, E-LKPD, Konstruktivisme Â